2019
DOI: 10.1177/0886260519881522
|View full text |Cite
|
Sign up to set email alerts
|

Social Trust and Reciprocity Among Adolescent Girls Exposed to Interpersonal Violence

Abstract: Trauma research has traditionally focused on altered emotion regulation and its role in psychopathology, whereas mechanisms of social behavior remain comparatively unexplored, particularly among adolescents. It has been previously reported that adolescents with histories of interpersonal violence (IV) demonstrate disrupted social learning, and the degree to which they are impaired during social interactions requiring trustful behaviors may be associated with their levels of anxiety. In the present study, 52 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This finding is in line with previous findings on higher self-reported levels of distrust in individuals with CM of varying age groups [14][15][16][17]. It contrasts a study that found no difference between girls with and without a history of physical or sexual abuse in the trust game [18]. It is possible that this discrepancy reflects the usefulness of assessing CM continuously rather than using between-groups approaches that set somewhat arbitrary thresholds of presence vs. absence of CM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with previous findings on higher self-reported levels of distrust in individuals with CM of varying age groups [14][15][16][17]. It contrasts a study that found no difference between girls with and without a history of physical or sexual abuse in the trust game [18]. It is possible that this discrepancy reflects the usefulness of assessing CM continuously rather than using between-groups approaches that set somewhat arbitrary thresholds of presence vs. absence of CM.…”
Section: Discussionsupporting
confidence: 90%
“…Lower trust is indicated by smaller monetary contributions or investments in the interaction partner (i.e., expecting that one's contribution will not be repaid and that one's trust will be broken). One study found that girls with and without a history of physical or sexual abuse showed similar monetary contributions in the trust game [18]. Contrasting this, adolescent girls with CM showed a lower ability to learn which individuals are trustworthy than non-exposed girls in the trust game.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations from normative change at the facet-level could help pinpoint more specific risk factors. For instance, youth exposed to interpersonal trauma struggle with trusting others (Gobin & Freyd, 2014; Neil et al, 2022; Sellnow et al, 2021), which may be reflected in a lack of normative increase in the trust facet (vs. impacting the entire agreeableness domain). The trajectory of the trust facet could, in turn, have lasting negative impacts on adult relationships (Nielsen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from normative change at the facet-level could help pinpoint more specific risk factors. For instance, youth exposed to interpersonal trauma struggle with trusting others (Gobin & Freyd, 2014;Neil et al, 2022;Sellnow et al, 2021), which may be reflected in a lack of normative increase in the Trust facet (versus impacting the entire Agreeableness domain). The trajectory of the Trust facet could, in turn, have lasting negative impacts on adult relationships (Nielsen et al, 2018).…”
Section: Implications Of Hierarchical Developmental Processesmentioning
confidence: 99%